Active Learning Research and Practice for STEAM and Social Sciences Education - Ortega-Sánchez, Delfín (Education and Human Development, 2022)
This book provides theoretical answers, applied methodological models, and didactic experiences that seek to reflect and analyze the potentialities and challenges of the active learning concept in STEAM disciplines and social sciences education. It also contributes to the understanding, intervention, and resolution of contemporary social problems and to the United Nations Sustainable Development Goals through the design, implementation, and evaluation of educational programs that incorporate integrated active learning as one of its explanatory axes.